Clinical and epidemiological characterization of congenital syphilis in neonates. Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga. (Boletin Médico de Postgrado, 2020)
A descriptive, cross-sectional study, of retrospective review of data from 102 medical charts was carried out in order to describe clinical and epidemiological characteristics of congenital syphilis in neonates registered at the Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga during the period January 2014 to June 2017. Male sex was predominant 52%, weight and height of newborns were between 2.501 to 4.000 grams and 46 to 55 cms, respectively; preterm and term neonates were of adequate size; APGAR score was normal at one, five and ten minutes. Most common clinical and paraclinical manifestations of congenital syphilis of the neonate at birth were jaundice (41,2%), leucocitosis (16,7%) and periostitis (12,8%). 78,4% had non-reactive VDRL in cerebrospinal fluid while 72,5% had reactive VDRL in blood. In conclusion, it is important to increase prenatal control and screen for maternal syphilis in order to detect early cases and prevent congenital syphilis.
Keywords: congenital syphilis; clinical; sociodemographic characteristics